Membangun Paradigma Relasi Menurut Ajaran Keselamatan Yohanes Calvin di Jemaat GMIM Alfa Omega Rinegetan - Talumingan, Givenly; Tamaweol, Roy; Suwetja, I Ketut (Jurnal Teologi Pambelum, 2025)
This research discusses building a relationship paradigm according to John Calvin’s teachings on Salvation in the GMIM Alfa Omega Rinegetan Congregation in Tondano Dua Region to answer problems in the congregation that are wrong in understanding the concept of relating as a congregation. So, the purpose of this research is so that congregation members can understand how the congregation relates to each other according to John Calvin’s teachings on salvation. From this problem, the researcher uses a qualitative research method, and the researcher conducted observations, interviews, then used sampling techniques and data analysis techniques to achieve the objectives of this research. From the results of this research, it was found that some congregations understand that in establishing relationships with others, what others do, that will also be done back to the person, in positive or negative terms.